Pengaruh proporsi dewan komisaris independen, reputasi auditor, dan leverage terhadap earning management pada perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia - Al Hasymi, Hasbi; Dp, Emrinaldi Nur; Azlina, Nur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aimed to examine the influence of independent commissariat council proportion, reputation of auditor and leverage to the earning management. Samples in this research are 16 mining companies listed at Indonesian Stock Exchange in the period of 2009 – 2012. The tools analysis used in this research is multiple linear regression. The result of this research show that (1) The reputation of auditor have negative impact to earning management, it is showed by the value of the examination significance of 0,000 < 0,05. (2) The independent commissariat council proportion does not significantly influence to earning management, it is showed by the value of the examination significance of 0,502 > 0,05. (3) The leverage does not have significantly influence to earning management, it is showed by the value of the examination significance of 0,195 > 0,05. (4) The reputation of auditor, independent commissariat council proportion, and leverage simultanly have significantly influence to earning management, it is showed by the value of the examination significance of 0,002 < 0,05. The value of R square is 0,185 which means that there is only 18,5% of the earning management variation which can explain by the indpendent commissariat council proportion, reputation of auditor and leverage.Keyword: earning management, reputation of auditor, independent commissariat council proportion, leverage